Review on pyrolysis of hardwood residue to Biofuel - Mazlan, M.A.F. (Trans Tech Publications Ltd, 2014)
In Malaysia, approximately 7 million tonne/year of rubber wood waste and 5 million tonne/year of acacia wood waste were generated in 2011. These hardwood residues could be utilized to produce biofuel through pyrolysis process. The aims of the paper are to study the fluidized bed pyrolysis system, determine the properties of pyrolytic bio-oil, and highlight the effect of biomass type, size and pyrolysis temperature on pyrolytic products distribution. Â© 2014 Trans Tech Publications, Switzerland.